EKSPERIMENTASI PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW DAN TEAMS GAMES TOURNAMENT (TGT) DITINJAU DARI KECERDASAN INTRAPERSONAL SISWA - Noor Hidayati; Mardiyana Mardiyana; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract. The aims of the research were to determine: (1) which one has better learning achievement, Jigsaw learning model, TGT, or conventional, (2) which one has better learning achievement, students with high, middle or low intrapersonal, (3) based on learning model, which one has better learning achievement, students with high, middle, or low intrapersonal intelligence, (4) based on intrapersonal intelligence, which one has better learning achievement, Jigsaw learning model, TGT, or conventional. The type of the research was a quasi-experimental research with  a 3 x 3 factorial design. The population was XI science  students  of Senior High School in Kudus regency on academic year 2013/2014. Sampling was done by stratified cluster random sampling. The size of the sample were 277 students consisted of 95 students in the first experimental group, 87 students in the second and 95 for the control class. The instruments used were mathematics  achievement test and  intrapersonal intelligence questionnaire. The hypotheses testing used unbalanced two ways ANOVA. Based on hypothesis testing, it can be concluded as follow. (1) Student learning achievement  treated by TGT  is better than Jigsaw  and conventional, and Jigsaw model is better than conventional, (2) Learning achievement of students who have high intrapersonal intelligence is better than students who have middle and low intrapersonal intelligence, and students who have middle intrapersonal intelligence is better than students who have low intrapersonal intelligence, (3) Based on  all types of learning models,    students who have high intrapersonal intelligence have better learning achievement than students who have middle and low intrapersonal intelligence, and students who have  middle intrapersonal intelligence have better learning achievement than student  who have low intrapersonal intelligence. (4)  For high intrapersonal intelligence, students learning achievement treated by TGT is better than Jigsaw, for both learning models,  Jigsaw  and conventional have the same learning achievement. For middle intrapersonal intelligence, students learning achievement treated by TGT  is better than conventional, while both learning models,  Jigsaw and conventional have the same learning achievement. For low intrapersonal intelligence,  conventional and TGT are better than Jigsaw, while both learning models, TGT and conventional have the same learning achievement.Keywords: Jigsaw, TGT,  intrapersonal intelligence, learning achievement.